Improving Child and Family Health through Growth and Development Screening, Nutrition Education, and Healthy and Hygienic Living Practices in Rejomulyo Village, Kediri City - Eva Agustina Yalestyarini; Heri Saputro; Intan Fazrin; Hengky Irawan (Universitas STRADA Indonesia, 2026)
One indicator of achieving good child and family health is optimal child growth and development. However, parents are often unaware of delays in their children’s development. Common disorders include physical growth, motor, language, and behavioral problems. Based on the 2023 Riskesdas survey, among 82,661 infants and toddlers weighed nationwide, the prevalence of underweight was 19.6%, consisting of 5.7% severe and 13.9% moderate malnutrition.Families with toddlers need adequate education to monitor and stimulate growth and development effectively. Promotive and preventive efforts through community service activities are important strategies to improve child health outcomes. This activity aimed to enhance family knowledge and support early detection of children’s growth, development, and nutritional status.The program was conducted on January 25, 2026, in Rejomulyo Village, Kediri City, targeting families with infants and toddlers. Activities included growth and development screening, nutritional status assessment, developmental stimulation through educational games, and education on Clean and Healthy Living Behaviors (PHBS), food safety, and child-friendly environments. Supporting tools included booklets, knowledge questionnaires, and the Pre-Development Screening Questionnaire (KPSP) instrument.The results showed high participant attendance and strong community enthusiasm. No cases of developmental delay or stunting were identified. Families’ knowledge regarding child health, nutrition, and PHBS improved after the intervention.This activity effectively increased family awareness of monitoring child growth and implementing healthy living practices to support optimal child development.